The Effect of Implementing Electronic Portfolios Using Google Sites on Students' Citizenship Skills - Moh. farid Nurhadi (Universitas Negeri Gorontalo, 2026)
This study raises the issue of technology utilization by students as a support for lectures with the aim of this study is whether there is an influence of the application of electronic portfolios with the use of Google Sites on students' Citizenship Skills. This study is a study with a quantitative approach with a Survey method, due to the use of questionnaires as the main instrument in the study. This study was conducted at the Abdul Muthalib Sangadji State Islamic University, Ambon, Department of Islamic Education Management with a population of 40 students consisting of 2 classes. Based on the characteristics of the population that are considered homogeneous, the researcher used a sampling technique with a Simple Random Sampling technique by conducting randomization based on a given draw. The sample obtained was 29 students. The research variables in this study are the independent variable, namely the effect of the application of e-portfolios with the use of Google Sites and the dependent variable, namely students' citizenship skills. The analysis used by researchers to determine the effect of each variable uses a simple regression analysis technique. This analysis technique was chosen by researchers because in addition to determining the effect of the application of electronic portfolios (X) on citizenship skills (Y). The calculation results show that the calculated F value = 13.951 with a significance level of 0.000 (0.000 0.05), so the regression model can be used to predict the citizenship skills variable or in other words, there is an influence of the Portfolio With Google Site (X) variable on the citizenship skills variable (Y).